Regression of dilated-hypokinetic hypertrophic cardiomyopathy by biventricular cardiac pacing. - Ashrafian, H; Mason, M; Mitchell, A (2007)
The evolution of hypertrophic cardiomyopathy (HCM) towards dilatation and hypokinesis is an increasingly recognized complication with a high incidence of adverse outcomes, including sudden cardiac death, requiring defibrillator implantation and cardiac transplantation. It is generally regarded as the irreversible 'burnt-out' end-stage manifestation of HCM. We report one of the first cases of profound regression of the dilated-hypokinetic state by the application of biventricular pacing and cardiac resynchronization therapy (CRT). Reviewing the literature on the role of pacing in HCM and the energetic rationale for CRT in HCM prompts us to suggest that further systematic studies are needed urgently to assess the role of CRT in HCM variants.